Brain white matter changes associated with urological chronic pelvic pain syndrome: multisite neuroimaging from a MAPP case–control study. Issue 12 (December 2016) - Huang, Lejian; Kutch, Jason J.; Ellingson, Benjamin M.; Martucci, Katherine T.; Harris, Richard E.; Clauw, Daniel J.; Mackey, Sean; Mayer, Emeran A.; Schaeffer, Anthony J.; Apkarian, A. Vania; Farmer, Melissa A.
Abstract : Abstract: Clinical phenotyping of urological chronic pelvic pain syndromes (UCPPSs) in men and women have focused on end organ abnormalities to identify putative clinical subtypes. Initial evidence of abnormal brain function and structure in male pelvic pain has necessitated large-scale, multisite investigations into potential UCPPS brain biomarkers. We present the first evidence of regional white matter (axonal) abnormalities in men and women with UCPPS, compared with positive (irritable bowel syndrome, IBS) and healthy controls. Epidemiological and neuroimaging data were collected from participants with UCPPS (n = 52), IBS (n = 39), and healthy sex- and age-matched controls (n = 61). White matter microstructure, measured as fractional anisotropy (FA), was examined by diffusion tensor imaging. Group differences in regional FA positively correlated with pain severity, including segments of the right corticospinal tract and right anterior thalamic radiation. Increased corticospinal FA was specific and sensitive to UCPPS, positively correlated with pain severity, and reflected sensory (not affective) features of pain. Reduced anterior thalamic radiation FA distinguished patients with IBS from those with UCPPS and controls, suggesting greater microstructural divergence from normal tract organization. Findings confirm that regional white matter abnormalities characterize UCPPS and can distinguish between visceral diagnoses, suggesting that regional axonal microstructure is either altered with ongoing pain or predisposes its development. Abstract : Supplemental Digital Content is Available in the Text.Women and men with chronic urological pelvic pain exhibit regional white matter changes in proportion to symptom severity that may aid phenotyping of urological pain.